Lavender Linguistics: Lexicon Used by Gay People in Bali For the Topic of Preferences - Renaldy, Maryon (Humanis, 2021)
This study aims to find out the lexicon and its meanings used by gay people in Bali for the topic of preference. The data was collected through qualitative methods by interviewing informants, recording, and note-taking as well as doing participatory observation to gay people from several places, nightclubs, and communities in Bali including Balijoe, and Mixwell bar in Seminyak, and Bali Peace Crew Community in Denpasar. The data was qualitatively analyzed and descriptively presented based on lavender linguistics, which according to William Leap, is a study about the language used by the queer community to communicate. The theories used are sociolinguistics theories proposed by Yule which are slang and speech varieties. It resulted in 10 lexicons were used by gay people in the level of word, phrase, and abbreviation to exchange information or communicate with the interlocutors. The meanings of each lexicon are influenced by participants, setting, topic, and function.